The problems of Trade Unionism in the light of the San Francisco general strike. Letter of W. Green to Charles S. Zimmerman [and] Reply of Charles S. Zimmerman to William Green (Dressmakers Union Local 22 I.L.G.W.U., 1934)
American labor faces the future.